2018
DOI: 10.3389/fimmu.2018.00971
|View full text |Cite
|
Sign up to set email alerts
|

Fish Lymphocytes: An Evolutionary Equivalent of Mammalian Innate-Like Lymphocytes?

Abstract: Lymphocytes are the responsible of adaptive responses, as they are classically described, but evidence shows that subpopulations of mammalian lymphocytes may behave as innate-like cells, engaging non-self rapidly and without antigen presentation. The innate-like lymphocytes of mammals have been mainly identified as γδT cells and B1-B cells, exert their activities principally in mucosal tissues, may be involved in human pathologies and their functions and tissue(s) of origin are not fully understood. Due to sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 108 publications
(132 reference statements)
2
56
0
1
Order By: Relevance
“…In teleost fish, the fact that no cognate GCs are ever organized and there is no CSR seem to account for the low affinity maturation of antibodies during the primary and secondary immune responses observed in these species (56,57). Furthermore, a substantial amount of evidence has been gathered by different authors in recent years pointing to a phenotypic and functional resemblance between fish IgM + B cells and mammalian B1 cells (58)(59)(60)(61). In this context, under the mammalian paradigm that long-lived memory responses are only achieved through TD class-switched responses mounted within GCs, it would seem plausible to predict that teleost fish are not able to mount long-lived B cell memory responses.…”
Section: Discussionmentioning
confidence: 99%
“…In teleost fish, the fact that no cognate GCs are ever organized and there is no CSR seem to account for the low affinity maturation of antibodies during the primary and secondary immune responses observed in these species (56,57). Furthermore, a substantial amount of evidence has been gathered by different authors in recent years pointing to a phenotypic and functional resemblance between fish IgM + B cells and mammalian B1 cells (58)(59)(60)(61). In this context, under the mammalian paradigm that long-lived memory responses are only achieved through TD class-switched responses mounted within GCs, it would seem plausible to predict that teleost fish are not able to mount long-lived B cell memory responses.…”
Section: Discussionmentioning
confidence: 99%
“…The cod EV also contains C-reactive protein, histone H3, galectins and profilin, in addition to other proteins [71]. Given that there are numerous other (immune) proteins in the EVs, they should be given further attention, with regards to their induction and release during immersion vaccination [72].…”
Section: Mucosal Immune Responsementioning
confidence: 99%
“…As in mammals, Zebrafish has a well-maintained adaptive immune system composed of T and B lymphocytes that develop from the thymus and kidneys respectively. However, in relation to the development of memory lymphocytes, fish seem to have memory cells of the type B and T [78]. Yet, there has not been enough data to confirm that in Zebrafish.…”
Section: Zebrafish Model and Vaccines Testing Vaccination Safetymentioning
confidence: 99%
“…Therefore it was suggested that activation-induced deaminase and affinity maturation contributed to the diversification of antibodies also in fish [56]. Immunization of teleost fish with the TNP-KLH antigen (linked to trinitrophenyl to keyhole limpet hemocyanin), for example, induced the production of specific low affinity antibodies, which were replaced in 5 weeks by antibodies of intermediate affinity, and after 15 weeks, by antibodies with greater affinity for the antigen [28,97].…”
Section: Zebrafish Model and Vaccines Testing Vaccination Safetymentioning
confidence: 99%